English as "Lingua Franca" and the Internationalization of Academe - Rostan, Michele (International Higher Education, 2011)
English has become the major language of scientific communication, and to a lesser extent, teaching worldwide. Using data from a international study of the academic profession, this article discusses some of the themes, positive and negative, of the role of "global English.